Pembelajaran Menulis Teks Dengan Strategi Peta Konsep Untuk Meningkatkan Prestasi Belajar Pada Siswa Kelas VII-3 SMPN 2 Peusangan Siblah Krueng Bireuen - Suryani Suryani (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2015)
The problem examined was how student learning outcomes in observation text writing could be increased through the use of the concept map strategy in ClassVII-3 of SMP N 2 Peusangan Siblah Krueng, Bireuen. This study aimed to improve student learning outcomes in observation text writing using the concept map strategy in Class VII-3 of SMP N 2 Peusangan Siblah Krueng, Bireuen. The approaches used in this study were the qualitative research hand the Class Action Research (PTK). Data collected in the study came from the pre-testand post test, observation, and field notes. Techniques of data analysis were data reduction, data collection, and drawing conclusions. The results showed that the implementation of the Indonesian language learning can enhance the activities of teachers and students. The results of observations ofthe activities of teachers and students in the implementation of the cycle I action obtained an average percentage of 73.7%. However, in terms of the results, the implementation of the first cycle had not been successful because the students obtaining the score of â‰¥ 65 were only16 students, with the class completeness of 80%. Thus, the researcher conducted arepetition cycle, and was successful. The results ofobservations ofteachers and studentsinthe second cycle earned the average percentage of 83.3%, and reached 89.2% of classical completeness. Further more, in terms ofthe results, the implementation ofthe second cycleshowedthat theimplementation of the Indonesian language learning with the concept map scould improve the student achievement in Writing Observation Text. This can be seen from the percentage of students who received â‰¥ 65 classically were 89.2%, with the class average of 83.3. Thus, the concept map strategy applied can enhance the activities of teachers and students in learning Indonesian on Writing Observation Text in Class VII-3 of SMP N 2 Peusangan Siblah Krueng, Bireuen district. Kata kunci: teks observasi, prestasi, dan strategi peta konsep